Odpowiedzi

2009-09-10T17:06:26+02:00
A)18-(-12)+(-5)=18+12-5=25
b)-8+(-12)-(-6)= -8-12=6=14
c)16-(-18)+(-24)-(-35)=16+18-24+35=45
d)-6+(-17)-(-22)+(-5)-1= 6-17+22-5-1=5
e)12-(-6)+(-18)-(-3)=12+6-18+3=3
f)-(-4)+(-7)-(-4)-(+3)= 4-7+4-3=-2
g)-7-9+(-6)-(-(9)= -7-9-6-(-9)=-7-9-6+9=-13
2009-09-10T17:57:05+02:00
A)18+12-5=25
B) -8-12+6= - 14
C) 16+18-24+35= 34-24+35= 10+35=45
D) -6-17+22-5-1= -29+22 = -7
E) 12+6-18+3= 18-15=3
F) 4-7+4-3=-2
G) -7-9-6+9 = -13
Pamiętaj minus i minus dają plus a minus i plus dają minus.